Profiling the Atlantic Salmon IgM+ B Cell Surface Proteome: Novel Information on Teleost Fish B Cell Protein Repertoire and Identification of Potential B Cell Markers - Peñaranda, Ma. Michelle D.; Jensen, Ingvill; Tollersrud, Linn G.; Bruun, Jack-Ansgar; Jørgensen, Jorunn B. (Frontiers in Immunology, 2019)
Fish immunology research is at a pivotal point with the increasing availability of functional immunoassays and major advances in -omics approaches. However, studies on fish B cells and their distinct subsets remain a challenge due to the limited availability of differentially expressed surface markers. To address this constraint, cell surface proteome of Atlantic salmon IgM+ B cells were analyzed by mass spectrometry and compared to surface proteins detected from two adherent salmon head kidney cell lines, ASK and SSP-9. Out of 21 cluster of differentiation (CD) molecules identified on salmon IgM+ B cells, CD22 and CD79A were shortlisted as potential markers based on the reported B cell-specific surface expression of their mammalian homologs. Subsequent RT-qPCR analyses of flow cytometry-sorted subpopulations from head kidney leukocytes confirmed that both cd22 and cd79a genes were highly expressed in IgM+ lymphoid cells but were observed in barely detectable levels in IgM- non-lymphoid suspension and adherent cells. Similarly, significantly high cd22 and cd79a mRNA levels were observed in IgM+ or IgT+ lymphoid cells from the spleen and peritoneal cavity, but not in their corresponding IgM- IgT- non-lymphoid fractions. This suggests that the B cell restrictive expression of CD22 and CD79A extend down to the transcription level, which was consistent across different lymphoid compartments and immunoglobulin isotypes, thus strongly supporting the potential of CD22 and CD79A as pan-B cell markers for salmon. In addition, this study provides novel information on the salmon B cell surface protein repertoire, as well as insights on B cell evolution. Further investigation of the identified salmon CD molecules, including development of immunological tools for detection, will help advance our understanding of the dynamics of salmon B cell responses such as during infection, vaccination, or immunostimulation.